Shhhh...listen! do you hear the sound of hrperlocal news in social media? - Mior Kamarulbaid, Afiqah; Wan Abas, Wan Anita; Omar, Siti Zobidah; Bidin, Rosmiza (Zes Rokman Resources, 2018)
This paper aimed to understand the types of news and sources that have been distributed in hyperlocal news pages on social media. Changes in news on social media news have attracted many scholars of journalism and new media to study on news literacy in social media. The development of social media as a news outlet has made many researchers question whether social media is capable of creating and distributing news to the society, especially on local news. In journalism, researchers take into account the character and types of the news and content they received, for instance a comparative analysis between Siakap Keli (alternative media) and Harian Metro (professional media) that cover local news was carried out in this study. This article aims to contribute to the broadening of our views on hyperlocal media in social media news pages. Firstly, researchers showed what news criteria of hyperlocal news are covering on social media. Secondly, this research discussed the news sources role of hyperlocal media in covering local news and news with beats that guide hyperlocal journalists determining the types of leads and story organization. The findings showed that hyperlocal media news pages in Malaysia are not only focused on the local content only but also encouraging news literacy among the local public on events around them.